The role of the tumor microenvironment in endocrine therapy resistance in hormone receptor-positive breast cancer - Yuan, Jie; Yang, Li; Li, Zhi; Zhang, Hua; Wang, Qun; Huang, Jun; Wang, Bei; Mohan, Chakrabhavi Dhananjaya; Sethi, Gautam; Wang, Geng (Frontiers in Endocrinology, 2023)
Endocrine therapy is the prominent strategy for the treatment of hormone-positive breast cancers. The emergence of resistance to endocrine therapy is a major health concern among hormone-positive breast cancer patients. Resistance to endocrine therapy demands the design of newer therapeutic strategies. The understanding of underlying molecular mechanisms of endocrine resistance, components of the tumor microenvironment (TME), and interaction of resistant breast cancer cells with the cellular/acellular components of the intratumoral environment are essential to formulate new therapeutic strategies for the treatment of endocrine therapy-resistant breast cancers. In the first half of the article, we have discussed the general mechanisms (including mutations in estrogen receptor gene, reregulated activation of signaling pathways, epigenetic changes, and cell cycle alteration) responsible for endocrine therapy resistance in hormone-positive breast cancers. In the latter half, we have emphasized the precise role of cellular (cancer-associated fibroblasts, immune cells, and cancer stem cells) and acellular components (collagen, fibronectin, and laminin) of TME in the development of endocrine resistance in hormone-positive breast cancers. In sum, the article provides an overview of the relationship between endocrine resistance and TME in hormone-positive breast cancers.